Lens changes in cardiovascular catheterization laboratories staff - César Hernández; Flor E. Gómez; María C. Cortés; Mariana Cabrera; Claudia R. Carvajal; Shirley M. Rosenstiehl; Hernán A. Ríos (Revista Colombiana de Cardiología, 2019)
Objective: to determine the association between occupational ionizing radiation exposure in the cardiovascular catheterization laboratories staff and development of lens changes. Methods: a cross-sectional study was made. Participants were recruited at the XIII Colombian Conference of Interventional Cardiology and SOLACI conferences in Bogotá - Colombia 2017. Informed consent was obtained from all study participants. Demographics and clinical data were collected. Associated lens changes were determined according to the ionizing radiation exposure status. Results: a total of 89 subjects (178 eyes) participated in the study. In general, the mean age was 40 years old, ranging from 19 to 78 years old. Distribution according gender was 55.3% male and 44.7% female. 31 subjects (62 eyes) were deemed to have not occupational exposure to radiation and 58 subjects (116 eyes) with a history of occupational radiation exposure. Exposed eyes had twice risk for present subcapsular posterior lens opacity compared to non-exposed eyes. The subjects with older age and physician role were associated to the presence of lens opacity, with a p value 0.001 in both cases. Likewise, exposed subjects with any lens opacity had a high mean occupational lifetime, with a p 0.001. Conclusions: this study confirms a statistically significant increase in radiation-associated subcapsular lens changes in the eyes of interventional cardiology staff compared to unexposed controls. Resumen: Objetivo: determinar la asociación entre la exposición a radiación ionizante en el personal de las salas de cateterismo cardiovascular y el desarrollo de cambios en el cristalino. Métodos: se hizo un estudio transversal. Los participantes fueron reclutados en el XIII Congreso Colombiano de Cardiología Intervencionista y las Conferencias SOLACI en Bogotá - Colombia 2017. Se obtuvo el consentimiento informado de todos los participantes. Se recolectaron datos demográficos y clínicos. Se determinó la asociación entre los cambios en el cristalino y la exposición a la radiación ionizante. Resultados: un total de 89 sujetos (178 ojos) participaron en el estudio. En general, la edad promedio fue de 40 años, con edades comprendidas entre los 19 años y 78 años. La distribución según el género fue del 55,3% en hombres y el 44,7% en mujeres. Se consideró que 31 sujetos (62 ojos) no tenían exposición ocupacional a la radiación y 58 sujetos (116 ojos) presentaban exposición ocupacional a esta. Los ojos expuestos tenían dos veces el riesgo de presentar opacidad subcapsular posterior del cristalino en comparación con los ojos no expuestos. Los sujetos de mayor edad y con rol de médico se asociaron a la presencia de opacidad del cristalino, con un valor p de 0.001 en ambos casos. Del mismo modo, los sujetos expuestos con cualquier opacidad del cristalino tenían una vida laboral más larga, con una p 0.001. Conclusiones: este estudio confirma un aumento estadísticamente significativo en la presencia de cambios en el cristalino en el personal de las salas de cateterismo cardiovascular en comparación con los controles no expuestos. Keywords: Ionizing radiation, Occupational exposures, Lens opacity, Palabras clave: Radiación ionizante, Xposición ocupacional, Opacidad del cristalino